The Cambridge Introduction to Shakespeare’s Tragedies - Dillon, Janette (Apress, 2013)
Imagine that, as in the current vogue of Saturday night British television, you are watching the Top 100 Shakespearean TragicMoments.What will reach the top five? Macbeth clutching at an imaginary dagger? Lear with Cordelia in his arms? Cleopatra holding the asp to her breast? Juliet falling on Romeo’s body? Number one would surely have to be one of two iconic moments fromHamlet: ‘Alas, poor Yorick’ or ‘To be or not to be’. Do these moments have anything in common that helps us towards a definition of Shakespearean tragedy? The only more or less common factor is perhaps a relentless focus on the solitary individual; but this may be less an effect of Shakespearean tragedy itself than of a post-Romantic way of reading Shakespearean tragedy almost solely through the lens of the tragic hero